2009
DOI: 10.1590/s0102-695x2009000300009
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação in vivo do efeito hipocolesterolêmico e toxicológico preliminar do extrato bruto hidroalcoólico e decocção da Vitex megapotamica (Spreng) Moldenke (V. montevidensis Cham.)

Abstract: Unitermos: Vitex megapotamica, Lamiaceae, hipocolesterolemia, hipotrigliceridemia.ABSTRACT: "Evaluation of prospective hypocholesterolemic effect and preliminary toxicology of crude extract and decoction from Vitex megapotamica (Spreng) Moldenke (V. montevidensis Cham.) in vivo". The cardiovascular diseases are, in general, associated with high levels of serum lipids which have high incidence in middle-age men and women. Among other properties characterized by popular medicine, the Vitex megapotamica (Spreng) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 8 publications
1
4
0
1
Order By: Relevance
“…In addition to activities directly renoprotective, MEVM treatment was able to reduce the TC levels in LDLr-null mice without affecting the elevation of HDL levels. Furthermore, a significant reduction in serum triglyceride was also observed, as previously reported [ 7 ]. Treatment with the highest dose of MECS showed significant reduction in the atherosclerotic index serum (AIS), with potential cardiovascular and renoprotective effect of this species.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition to activities directly renoprotective, MEVM treatment was able to reduce the TC levels in LDLr-null mice without affecting the elevation of HDL levels. Furthermore, a significant reduction in serum triglyceride was also observed, as previously reported [ 7 ]. Treatment with the highest dose of MECS showed significant reduction in the atherosclerotic index serum (AIS), with potential cardiovascular and renoprotective effect of this species.…”
Section: Discussionsupporting
confidence: 87%
“…In folk medicine, the infusion of the leaves of this plant is used in the treatment of hemorrhoids, hypertension, and as diuretic, hypocholesterolemic, anti-inflammatory, among other therapeutic properties [ 5 , 6 ]. This species has been characterized due to the presence of various substances of pharmacological interest, such as tannins, flavonoid glycosides, polyphenols, alkaloids, saponins, and essential oils [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of steroids and iridoids (Rimpler, 1969;Rimpler, 1972), a hypoglycemic activity of the leaves of V. megapotamica (Zanatta et al, 2007), the hypolipidemic effect of the crude hydroalcoholic extract and the decoction of the bark, including their contribution in reducing serum levels of cholesterol and triglyceride (Brandt et al, 2009), have been reported for the species under study.…”
Section: Introductionmentioning
confidence: 99%
“…10 e em 2009, foi demonstrado a ação do extrato bruto hidroalcóolico e decocção das cascas sobre efeito hipolipidêmico e redução dos níveis séricos de colesterol e triacilglicerol. 11 Estes mesmos autores realizaram um estudo fitoquímico preliminar do extrato bruto das folhas de V. megapotamica que revela a presença de taninos, glicosídeos flavonônicos, polifenóis, alcalóides, óleos essências e saponinas. Sendo assim, devido à escassez de estudos que comprovem tais efeitos, este estudo teve como objetivo realizar uma análise farmacognóstica dos extratos de V. megapotamica em diferentes solventes.…”
Section: Introductionunclassified